Symbols and Forms of Satanism Represented in Travis Scott Concert, Astroworld Festival 2021 - Tasya Rahmadina; Muhammad Husni Ritonga (PT Mattawang Mediatama Solution, 2022)
The purpose of this research is to depict the symbols and forms of Satanism in the Travis Scott concert. Due to riots that occurred during the concert a few months ago, 8 people were declared dead and hundreds of others were injured. However, many conspiracy theories emerged from netizens, who thought the concert was a ritual of human sacrifice because many netizens saw elements of satanism at the concert. As a result, the writer is intrigued by the images and shapes discovered by the researchers at this concert. The researcher will describe denotatively, connotatively, and mythically using Roland Bathers semiotics. Researchers discovered Satanic symbols and forms in Travis Scott's Astroworld Festival 2021 concert.